Diffraction Plane Dependence of Micro Residual Stresses in Uniaxially Extended Carbon Steels - T. Hanabusa; A. Shiro; M. Refai; M. Nishida (PPIKSN-BATAN, 2010)
In the stress measurement using X-ray or neutron diffraction, an elastic anisotropy as well as a plastic anisotropy of crystal must be carefully considered. In the X-ray and neutron diffraction stress measurement for polycrystalline materials, a particular hkl plane is used in measuring lattice strains. The dependence of an X-ray elastic constant on a diffraction plane is a typical example caused by an elastic anisotropy of the crystal. The yield strength and the work hardening rate of a single crystal depend on a crystallographic direction of the crystal. The difference in the yield strength and the work hardening rate relating to the crystallographic direction develops different residual stresses measured on each hkl diffraction after plastic deformation of a polycrystalline material. The present paper describes the result of the neutron stress measurement on uniaxially extended low and middle carbon steels. A tri-axial residual stress state developed in the extended specimens was measured on different kind of hkl diffraction plane. The measurement on the 110, 200 and 211 diffraction showed that residual stresses increased with increasing the plastic elongation and the residual stresses on 110 were compressive, 200 were tensile and those on 211 were the middle of the former two planes. Received: 30 September 2010; Revised: 28 October 2010; Accepted: 1 November 2010